PEMAHAMAN SURAT-SURAT PENDEK AL-QUR’AN TENTANG TOLERANSI DAN IMPLIKASINYA BAGI PENGEMBANGAN SIKAP PLURALISME - Syah, Darwyan (Analisis: Jurnal Studi Keislaman, 2013)
This  study  aims  to   describe  the  level  of understanding  short letters of the Qur’an about tolerance and pluralism attitude;  and analyze the effects of short letters of understanding Qur’an about tolerance  towards  pluralism  attitude.  This  research  on religius junior secondary school students Nurul Yaqin Ciledug Tangerang City  Banten  Province.  The  instrument  for understanding  short letters   of  the  Qur’an  about  tolerance   using  multiple   choice test with three option. Pluralism attitude instrument using a questionnaire  with  three  options.  The results  show: Firstly,  the level of understanding  short letters of the Qu’an about tolerance reaches 74.31 % in the high category  and the level of pluralism attitude  reaches 82.48 % included in the high category. Secondly there is positive and significant understanding of short letters of the Qur’an about tolerance towards pluralism attitude.  The influence understanding  of short  letters  of the Qur’an about  tolerance  to pluralism  attitude  of 29.52 % . The rest is influenced  by other factors remains to be investigated. The higher understanding  of short letters of the Qur’an about tolerance the higher attitude  of pluralism. Increased pluralism student attitudes can be improved through an increased understanding of the short letters of the Qur’an about tolerance.